Keelebarjäär tervishoius: kahjulik patsiendi tervisele, kurnav tervishoiutöötajale ja kallis riigi rahakotile - Remmelg, Anette; Rõigas, Johanna; Poolamets, Doris; Sitsi, Anett; Põllu, Maarit; Hiie, Egert (Eesti Arst, 2026)
Eesti Arst 2026; 105(1):42–49